Digital Labour In The Live Streaming Economy: A Thematic Literature Review - Pardomuan Pardosi; Tussi Sulistyowati; Khairil Anwar; Leny Susilawati Anggraini; Jainuddin Jainuddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This article undertakes a systematic literature review using a qualitative descriptive method to synthesise existing evidence on digital labour in the live streaming economy. Data were retrieved from the Scopus database on 15 June 2025 using focused Boolean search terms related to digital labour, platform labour, and live streaming. Of 116 initial records, 29 articles published between 2020 and 2025 met the inclusion criteria and were screened based on PRISMA 2020 standards for methodological rigour.The results show that live streaming creators labour under unstable and typically exploitative conditions imposed by platform algorithms and managerial authority. Despite these tensions, creators demonstrate agency through building peer networks,leveraging authenticity,and using community-based strategies of negotiating sponsor and audience expectations. Brokerage strategies, family solidarity, and mutual support serve to cushion precarity and enable autonomy. These findings suggest that creator agency is not an outcome of platforms as such, but of creators' adaptive strategies and social resilience. This review contributes to a larger understanding of the ways in which digital labour is organized, experienced, and contested on live streaming platforms.